Penerapan Manajemen Bandwidth Dengan Metode Peer Connection Queue (PCQ) Menggunakan Queue Tree Di PT Duta Palma Nusantara, Kabupaten Kuantan Singingi Provinsi Riau. - Okpi Pranata Reskha; Noveri Lysbetti Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
PT. Duta Palma Nusantara is a Palm Oil Plantation Company in Kuantan Singingi Regency, has an office to handle information activities ranging from receiving and sending data on palm production using the internet network. The background of this research is uneven Bandwidth allocation on each computer and results in one user can access the internet faster while other users are slower than other users. Therefore, the Peer Connection Queue (PCQ) Method is used using the Queue Tree feature, so that users get evenly distributed Nandwidth. Testing using Microtic Devices, Winbox Software as a configuration. The test results showed that the quality of network bandwidth management using the Peer Connection Queue (PCQ) method on the Queue Tree feature gave better results than without using the PCQ Method because bandwidth was divided according to the rules applied and no Client gets Over Bandwidth as specified. Keywords: Bandwidth, Bandwidth Management, Peer Connection Queue (PCQ), Queue Tree.